Peningkatan Mutu Briket dari Sampah Organik dengan Penambahan Minyak Jelantah dan Plastik High Density Polyethylene (HDPE) - Silvia Septhiani; Eka Septiani (Syarif Hidayatullah State Islamic University, 2015)
The objective of this research was to looking for the alternative fuel to overcome the limitations of natural resources by using organic garbage and to investigate the improvement quality of biobriket after HDPE and cooking oil addition. Making biobriket with carbonitation organic garbage was a method that is used. The result of the research suggests that the quality of biobriket increased after HDPE and cooking oil addition. The analysis of water biobriket showed that HDPE was decreased from 13.99% to 13.88% and biobriket of cooking oil is 9.39%. More over the decreasing also happened to the content of the ash, from 25% to 23% biobriket HDPE and 20% to biobriket of cooking oil. Calorific biobriket 4703.27 cal/g, the increasing of HDPE biobriket was 5009.16 cal/g and biobriket of cooking oil 6245.66 cal/g. DOI :http://dx.doi.org/10.15408/jkv.v0i0.3567.